A systematic review of post-stroke fatigue measurement scale based on COSMIN guidelines - Wu, Lingsha; Jin, Haiqin (Frontiers in Neurology, 2024)
Objective This study aimed to evaluate the methodological quality and measurement attribute quality of the post-stroke fatigue measurement scale, so as to provide some basis for the clinical application and promotion of related scales. Methods The Chinese National Knowledge Infrastructure, the Wanfang Data Knowledge Service Platform, the China Science and Technology Journal Database, the Chinese Medical Journal Full-text Database, the Chinese Biology Medicine, PubMed, Embase, Medline, the Cochrane Library, the Web of Science, CINAHL, and PsycINFO databases were searched for literature on the post-stroke fatigue measurement scale up to June 2022. Literature screening and data extraction were carried out independently by two researchers, and in the case of disagreement, discussions were held with a third investigator to reach an agreement, and the COSMIN checklist and criteria were used to systematically evaluate the attributes of the measurement scale. Results A total of 17 studies were included, involving 10 post-stroke fatigue measurement scales. The content validity of FSS-7, FACIT-F, NRS-FRS, and MFI-20 was “not mentioned,” and the remaining scales were “uncertain.” In terms of construct validity, MFS was “adequate”; FSS-7, FACIT-F, and NRS-FRS were “not mentioned”; and the remaining scales were “uncertain.” In terms of internal consistency, NRS-FRS was “not mentioned”; FSS and MFS were “adequate”; and the remaining scales were “uncertain.” In terms of hypothesis testing, CIS and FACIT-F were “not mentioned,” NRS-FRS was “adequate,” and the remaining scales were “uncertain.” The stability of FSS-7, CIS, FACIT-F, and MFI-20 was “not mentioned,” and the remaining scales were “adequate.” The cross-cultural validity of FSS-7 was “adequate,” and the remaining scales were “not mentioned.” All 10 scales were given a recommendation grade of “B”. Conclusion For the time being, the FSS can be recommended to measure post-stroke fatigue, but it still needs to be tested for more relevant measurement properties in order to gain more support from high-quality evidence. For a more comprehensive assessment of post-stroke fatigue, the FIS, FAS, and NFI-stroke should perhaps be considered, as the FSS is a one-dimensional scale that can only measure physical fatigue in patients; however, these scales also need to be tested for more relevant measurement properties to verify their clinical applicability.